Bond strength of a composite resin to glass ionomer cements using different adhesive systems - Ana Carolina de Oliveira BECCI; Mônica de Souza BENETTI; Natália Bertolo DOMINGUES; Elisa Maria Aparecida GIRO (Universidade Estadual Paulista, 2017)
Abstract Introduction Glass ionomer cements are often used as a base or cavity lining prior to restorative material. Objective To evaluate the bond strength of a composite resin to different glass ionomer cements, when using a two-step conventional and self-etching adhesive systems. Material and method Three glass ionomer cements (Ketac Molar Easymix, Vitremer and Vitrebond), the composite resin Filtek Z350 XT and the adhesive systems Adper Single Bond 2, Clearfil SE Bond and Adper Easy One were used. As negative control, resin was bonded to cement without using an adhesive system. Holes (4 mm diameter, 2 mm deep) prepared in acrilic bloks were filled with the glass ionomer cements (n=12/group). On the surface, an area of 1mm in diameter was delimited, the adhesive system was applied, and a specimen of composite resin with 1 mm height was made. After 24 hours storage (37 °C and 100% humidity), the microshear test was performed. Data were analyzed using two-way ANOVA and Tukey test for comparison between groups (α=0.05). Result The adhesive systems significantly improved the bond strenght of composite resin to glass ionomer cements (p≤0.001). There was no significant difference in bond strength when self-etching adhesive systems were compared with the simplified etch-and-rinse adhesive, except for Vitrebond where Clearfil SE Bond determined higher bond strength when compared to Adper Single Bond 2 (p=0.003). Conclusion Self-etching adhesive systems are a good option for establishing the bond between the composite resin and the glass ionomer cement.